Experimentation of the Effectiveness of Social Adjustment in Professional Education - S. T. Tursunov (International Journal on Integrated Education, 2022)
In this article, new issues related to the education and upbringing system as an objective component in the social adaptation of students in the professional education system are highlighted. The impact of social principles on the adaptation of young students in new life and socio-economic conditions during vocational education is scientifically based. An analysis of pedagogical factors reflecting the level of preparation of students and educational activities in a professional educational institution is presented.